Current trend in geoinformation technology - A. Kadir, Abd. Majid; Ses, Shahrum; Desa, Ghazali; Omar, Kamaludin; Omar, Abdullah Hisam; Chen, Kah Eng; Wong, Yeak Kuan (2001)
A collaborative study between the Department of Survey and Mapping Malaysia (DSMM), the Universiti Teknologi Malaysia (UTM), the University College London (UCL), and the University of New South Wales (UNSW) on the feasibility of implementing CCS in Malaysia has been completed in 1999. Outcomes from the feasibility study call for further research regarding the development of the implementation plan for CCS in Malaysia.